Tropical Tasar Silk: a Pontential NTFP for Forest Dwellers of Central India - Roychoudhury, N.; Bajpai, Rajesh; Singh, B. P. (Indian Forester, 2011)
Tropical tasar silk, a major components of wild silks, popularized in India as "Vanya Silk", is one of the most important NTFPs that produced in nature by caterpillars of a sericigenous insect, Antheraea mylitta Drury (Lepidoptera: Saturniidae). It is commercially exploited for wild silk production in India by aboriginals residing in the central plateau mainly Jharkhand, Bihar, Chhattisgarh, Madhya Pradesh, Orissa, West Bengal, Uttar Pradesh, Andhra Pradesh and Maharashtra. This insect has a long list of 20 host plants but reared mostly on sal (Shorea robusta Roxb.) arjun (Terminalia arjuna Bedd.) and asan (T. tomentosa W.&A.), in the natural forests or plants systematically developed in degraded forest areas. Sal forests provide base for the collection of a large quantity of naturally grown cocoons, Tasar silkworms are reared outdoors and are predominantly bivoltine and trivoltine in nature. The first crop is raised during July-August (seed crop) whereas second crop is reared during September-October (commercial crop). The average annual income due to the collection of tasar cocoons in central India is estimated to be low as compared to that of other tasar states. The probable reasons are scattered distribution of food plants on which the silkworm grows, the absence of profitable plantations, lack of suitable breed and proper knowledge of breeding and multiplication techniques. Tropical tasar, a potential NTFP has vast potential in central India.